10 OPTIMALISASI LAYANAN INTEGRASI KENDARI (LAIKA) MENUJU KOTA LAYAK HUNI YANG BERBASIS EKOLOGI, INFORMASI DAN TEKNOLOGI - Syaiful Zainal, Andi; Murniati, Murniati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Kendari, 2021)
The purpose of this study is to determine the optimization of the Integrated Service in Kendari(LAIKA) in realizing Kendari City as a livable city based on ecology, information and technology. Toconduct the study, the method used is descriptive qualitative. The research findings reveal that theLAIKA program is an integrated program in sub-district that aims to facilitate the community inobtaining fast, accurate and affordable services. In its implementation, this program has not runoptimally yet. There are still various constraints, such as the internet network availability. Not allsub-districts can access the internet. Another problem comes from the community who use theservice. In general, people do not know about the program due to the lack of socialization from theKendari City government and especially from the village government.